Management of Complicated Crown-root Fractures Involving Permanent Maxillary Incisors in Children: Two Case Reports - Mallayya C Hiremath; Srinath Krishnappa; Vaishnavi K Kamath; Aditya S Naik (Journal of South Asian Association of Pediatric Dentistry)
Traumatic dental injuries (TDIs) are common in children and young adults, with maxillary incisors being most commonly affected. Crown-root fractures account for 5% of TDIs affecting permanent dentition. Management of these requires consideration of endodontic, periodontal, and restorative factors. Various treatment options are available that need to be chosen based on the clinical scenario. This article reports two cases of crown-root fractures in children, which were managed using a multidisciplinary approach. The two major challenges faced during the treatment were salivary contamination during endodontic treatment and subgingival fracture margins. These challenges were successfully managed, and the remaining tooth structure was preserved, which maintained the alveolar bone height around the area and prevented malalignment of the adjacent teeth. This also helped in the psychological and social well-being of the child.